Management of Al-Madinah Mosque Ciledug Tangerang - Sari, Diana; Guilin, Xie; Jiao, Deng (Journal International Dakwah and Communication, 2024)
Mosque management is carried out based on good planning. Apart from functioning as a place of worship, the mosque also fosters and educates humans to become believers and pious people. The Prophet set the mosque as a center of worship, resolving cases, as a center for education and teaching, setting strategies for the spread of Islam, information centers for Islamic activities, social places, placed baitul mal / state treasury, or Muslim community treasury, Ibn Sickle recited his rhymes in the mosque when defending the prophet, and marriage. And the mosque also has good management and a neatly arranged organization to carry out the functions of the mosque.